Biochar enhances anaerobic oxidation of methane coupled with Cr(VI) reduction: Pyrolysis temperature-dependent electron transfer pathways and regulatory mechanisms - Lianfu Liang; Yepu Li; Xiaofeng Fu; Rui Lin; Keying Liu; Zhiqiang Zhao (Bioresource Technology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Intermittent organophosphate pesticide exposure induces hepatic injury in goats with subclinical fatty liver via immune activation and energy metabolism reprogramming - Dechun Chen; Tianjun Yang; Ting Zhao; Anzhu Li; Qingjia Lin; Xinying Zhou; Huanrong Zhang; Jian Fu; Falong Yang; Haifeng Liu (Environmental Pollution, 2026)

Unveiling intricate interplay between Ni and Ce within microenvironment of NiCe/C@NC for electrocatalytic CO2 reduction - Zeyu Zhang; Huangdong Wang; Qian Zhao; Lin Jia; Yan Guo; Zewei Fu; Mengbo Zou; Guixiang Ma; Shangpeng Liu; Fenrong Liu; Shanghong Zeng (Chemical Engineering Journal, 2026)

MXene hollow microspheres with tunable sizes and heterostructures for high-efficiency broadband microwave absorption - Yan-Qin Wang; Lin Zhang; Hao Chen; Zi-Hao Wang; Fu-Rong Zeng; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Mechanism of Kushen Tongguan Pill on benign prostatic hyperplasia: roles of TLR4/NF-κB pathway and macrophage M1 polarization - Shaofeng Chen; Jie Wang; Yuhong Feng; Chunxu Li; Fu Wang; Lin Miao; Yaojun Li; Yangyang Lei; Qiang Geng; Zhong Li; Feng Zhao; Yuan Sun; et al. (Journal of Molecular Histology, 2026)

Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

A dynamic DNA nanoconstruct-integrated hydrogel: Reprogramming osteoimmune for diabetic bone defect repair - Mei Zhang; Xiao Fu; Zhen Zhao; Yiliu Zhou; Jiahui Xiong; Bo Huang; Yao He; Zhiqiang Liu; Yunfeng Lin (Chemical Engineering Journal, 2026)

High thermoelectric performance in Sm and Bi dual-doped GeTe with nuanced recrystallization annealing - Ge Fu; Shangchao Lin; Yixuan Liu; Yang Liu; Qilin Zhang; Jie Xiao; Changying Zhao (Chemical Engineering Journal, 2026)

Bamboo-Inspired bionic microfluidic Reactor: Construction and application for industrial Biocatalysis - Quan Zhou; Litao Wang; Zijing Zhao; Xi Lin; Jiandong Wang; Guosheng Liu; Zihui Cai; Chaobo Huang; Yujie Fu (Bioresource Technology, 2026)

Comparative plastid genomics of five Ormosia species (fabaceae): insights into structural variation and morphological homoplasy - Shihong Zhang; Fengcheng Deng; Yixiong Zhao; Jiating Wang; Dipak Khadka; Jieyu Lin; Yuhua Hu; Keyi Fu; Lei Jiang; Mingxuan Zheng; Shi Shi (Plant Systematics and Evolution, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Growth-mode-independent glutamine/glutamate/aspartate metabolic shift and urea cycle remodeling driven by FOXA1 in benzo[a]pyrene-transformed human bronchial epithelial cells - Yujin Fu; Yanmin Qi; Yunkun Xing; Yitong Lin; Zhiyu Liu; Juanling Fu; Biyun Yao; Peng Zhao (Toxicology and Applied Pharmacology, 2026)

Wendan decoction ameliorates chronic obstructive pulmonary disease via regulating pulmonary microbiota homeostasis and inhibiting NOD-like receptor pyrin domain-containing 3-Caspase1 pathway: Integrating chemical profiling, efficacy validation and molecular mechanism elucidation - Song Lin; Qi Yu; Guoan Zhao; Xuanyu Fu; Yuyang Chen; Shutong Chen; Ying Lyu; Weiwei Jia; Yuran Sun; Wenbao Wang; Tianyang Wang; Yan Lin (Food Bioscience, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Ultrahigh-resolution flexible quantum-dot light-emitting diodes via dual assembly and transfer printing - Xin Hu; Yangbin Zhu; Runzhen Sun; Zhen Wang; Jiayu Sun; Qinghong Lin; Yi Jiang; Hongyang Fu; Kejia You; Xuan Guo; Yue Wang; Deli Li; et al. (Chemical Engineering Journal, 2026)

From Geoheritage to Rural Revitalization: A Case Study of the Ru’an Geo-Cultural Village in Hainan Province, China - Jianweng Gao; Zhenliang Wang; Jingjing Gong; Jianzhou Yang; Yan’gang Fu; Lujun Lin; Zhuang Duan; Keqiang Zhao; Yong Li (Geoheritage, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Intracranial Mitochondrial Microparticles Promote Cerebral Edema via Endothelial Injury in Stroke - Xiaoyan Du; Xintong Yu; Mengfei Wang; Ying Fu; Kunxin Lin; Jiaying Wu; Qianqian Lin; Wenlong Zhao; Yi Lin (Translational Stroke Research, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

An integrated γ-aminobutyric acid–phytic acid strategy mitigates oxidative stress and quality deterioration in spinach during ambient-temperature storage - Shiai Zeng; Lan Gao; Kai Wang; Xuwei Liu; Peihong Fu; Lin Li; Lei Zhao (Food Bioscience, 2026)

Effects of PE microplastics on root morphology and soil nutrients with mechanisms of rhizosphere enrichment in Brassica rapa var. chinensis - Yifei Lin; Chenrui Zhao; Chengliang Li; Lei Hou; Na Liu; Yicheng Fu; Qian Zhang (Journal of Soils and Sediments, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Integrated analysis of dynamic changes in volatile and non-volatile compounds in Chuan Chenpi (Citrus reticulata ‘Dahongpao’) during aging by GC-IMS and UPLC-MS/MS - Jialiang Zou; Huangsheng Zhang; Liang Zhao; Huanhuan Xu; Lin Chen; Hongping Chen; Fu Wang; Yuan Hu; Youping Liu (Food Chemistry, 2026)

Multistage-enhanced stochastic inverse modeling approach for efficient source characterization of groundwater organic contamination - Zeyu Hou; Yifan Fu; Yingzi Lin; Ke Zhao; Tongzhe Liu; Wenxi Lu (Stochastic Environmental Research and Risk Assessment, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

Photocatalytic hydrogen production: Materials design, system engineering, and data-driven advances - Gengran Zhai; Junchen Liu; Shiyi Lin; Yifan Cheng; Bin Wang; Qingyao Jiang; Hongwei Fu; Hongxin Zhao; Yuan Lu (Chemical Engineering Journal, 2026)

Load mitigation in floating wind turbines via active tuned mass damper using a physics-informed neural network based controller - Jianing Fu; Shuyue Lin; Hongyang Dong; Xiaowei Zhao (Ocean Engineering, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Space weathering on the lunar nearside and farside revealed by iron and potassium isotopes - Heng-Ci Tian; Wei Yang; Xinmiao Zhao; Jun Du; Liyu Shan; Wen-Jun Li; Jing Wang; Xuhang Zhang; Yangting Lin; Xian-Hua Li; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

MdERF106 modulates malate accumulation in apple fruit by activating MdALMT9 - Xu Xu; Lin Zhao; Renzhi Gui; Weihong Fu; Sanhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Mercury isotope perspectives on vegetation-enhanced nickel mobilization and migration during laterite formation - Ruo-Lin Liu; Martin Yan Hei Li; Run-Sheng Yin; Mei-Fu Zhou; Jun-Hong Zhao (Geochimica et Cosmochimica Acta, 2026)

Scalable production of antioxidant ‘sandwich’ films from all-natural composites for inhibiting fruit browning - Jie Deng; Hao Fu; Xinhong Li; Jieping Liu; Yuancheng Zhang; Wenxin Zhao; Baofeng Lin (Food Chemistry, 2026)

Development and application of fluorescent immunoassay lateral flow Technology for the Detection of Prolamins in food - Xinyi Zhao; Qi Fu; Wenye Zhu; Hong Lin; Zhiyu Liu; Hao Wang; Phon Reno; Ziye Zhang; Yuhao Huang; Zhenxing Li (Food Chemistry, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Hybridization and incomplete lineage sorting characterize the evolutionary history of two East Asian clades of Stewartia (Theaceae) - Han-Yang Lin; Miao Sun; Jian-Jun Jin; Cheng-Xin Fu; Douglas E. Soltis; Pamela S. Soltis; Yun-Peng Zhao (Molecular Phylogenetics and Evolution, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Modulating NLRP3 Inflammasome Activity and Enhancing Cortical Synaptic Plasticity: Nanoparticulate Hydrogen’s Role in Relief of Post-traumatic Anxiety-like Behaviors in Rats - Lanxia Wu; Congwen Yang; Yiqin Ding; Xinru Liu; Hao Sun; Xue Li; Yining Lu; Lifen Liu; Qingyang Fu; Min Li; Yingshuai Wang; Yuehan Zhao; et al. (Molecular Neurobiology, 2026)

Spermidine enhances cold tolerance in tomato fruit by boosting antioxidant and energy metabolism synergy - Jian-Lin He; Shi-Yin Xie; Xiao-Dan Zhao; Da-Qi Fu (Food Research International, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Correction: Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2025)

Analysis of the AP2/ERF transcription factor family in Eriobotrya japonica and its role in exogenous melatonin-mediated regulation of salt stress - Ling Zhu; Fuhua Liu; Xin Lin; Tianyu Fu; Lin Zou; Yuanhai Pan; Rong Zou; Yang Zhao; Hanyao Zhang (Functional & Integrative Genomics, 2025)

Functional characterization of odorant binding proteins in Pharsalia antennata provides insights into diverse binding properties and the importance of C-terminal residues - Shu-Lin Li; Fu-Peng Li; Zi-Xuan Yang; Yu-Jie Zhao; Zhao-Qun Li; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Identification of rice taste quality markers using metabolomics techniques - Jun Shu; Weidan Guo; Kangzi Ren; Xiangjin Fu; Zhao Long; Qinlu Lin; Chun Liu; Jiangtao Li (Food Chemistry, 2025)

Dissecting the role of foulant-spacer interaction energy on membrane fouling with a collision-attachment-based Monte Carlo approach - Junxia Liu; Mingxin Peng; Bingzhi Liu; Wei Fu; Chenxi Lin; Zhiwei Tang; Dongsheng Zhao; Weiwei Huang; Tian Li (Desalination, 2025)

Breaking the monopoly of the Zn(002): Phosphoryl-heterocyclic co-adsorption to promote preferential exposure of Zn(101) crystal plane for dendrite-free Zn metal anodes - Haoran Lang; Chao Li; Jingxin Zhao; Chunyuan Xiong; Lieyuan Zhang; Yijia Luo; Qiaoji Zheng; Xin Tan; Hong Fu; Bingang Xu; Dunmin Lin (Chemical Engineering Journal, 2025)

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

Carbon footprint of China's healthcare system from a global perspective: A multi-dimensional hotspot assessment - Han Zhao; Weiyi Liao; Lin Fu; Mengzhen Zhao; Shangchen Zhang; Jiale Wu; Peipei Chai; Wenjia Cai (Sustainable Production and Consumption, 2025)

Light-driven CO2 reduction for acetate production by coupling photocatalyst CdS with acetogenic bacteria Clostridium aceticum: An insight into the electron transfer pathway - Bo Fu; Wei Lin; Hui Zhao; Shijian Yang; Jingyi Han; Qihao Cao; He Liu; Hongbo Liu; Jieshu Qian (Journal of Environmental Chemical Engineering, 2025)

Anode-free lithium metal batteries with enhanced durability: magnetron-sputtered lithiophilic bimetallic coatings on Cu current collectors - Shanyu Zhou; Youyan Liu; Zelong Ma; Zhencheng Huang; Hongshuai Cao; Jie Chen; Xiaowu Fu; Zhongqiu Fu; Jie Wu; Shunian Chen; Lin Chen; Jiakun Wu; et al. (Chemical Engineering Journal, 2025)

Active cellulose-based film with synergistic enhanced photothermal antibacterial effects by Fe-doped ZIF-8 and EGCG for efficient litchi preservation - Wenxin Zhao; Yuntong Liang; Yuancheng Zhang; Yongfu Deng; Hao Fu; Xu Yuan; Zhen Wang; Xiaohe Lu; Baofeng Lin (Chemical Engineering Journal, 2025)

Linking two types of breccias to sediment-hosted stratiform copper (SSC) and iron oxide-copper-gold (IOCG) deposits in the Kangdian metallogenic belt, SW China - Xue-Qing Yin; Xin-Fu Zhao; Zhi-Kun Su; Hai-Tao Lin; Zhi-Min Zhu; Wen-Lei Song; Martin Yan Hei Li; Kui-Dong Zhao (Mineralium Deposita, 2025)

Characterization of Gut and Gill Microbiomes in Fast-Growing Pacific White Shrimp Penaeus vannamei - Zhenqiang Fu; Qinglong Chen; Yinjun Ye; Huixin Zhao; Genmei Lin; Jianguo Lu (Journal of Ocean University of China, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Interfacial water masking agent: Dynamic synergistic regulation of anode and cathode for ultra-long-life aqueous zinc metal batteries - Bin Xie; Chao Li; Min Li; Lieyuan Zhang; Zhaodan Fu; Yijia Luo; Gehong Su; Xin Tan; Heng Zhang; Qiaoji Zheng; Yu Huo; Jingxin Zhao; et al. (Chemical Engineering Journal, 2025)

High-performance pseudocapacitive anodes: Precision engineering of MoO3 thin films on nickel microparticles-enhanced carbon cloth for advanced supercapacitors - Pingzhong Fu; Nan Zhao; Lin Deng; Maoxin Luo; Jian Huang (Chemical Engineering Journal, 2025)

Combined space cooling/heating and domestic hot water supply driven by data center waste heat: Complementary energy conservation, economic capacity optimization and generic analysis framework - Jun Bai; Xiaohui Wu; Xiaoyuan Chen; Zhiying Zhang; Lin Fu; Chunxiao Zhao; Ke Qing; Qiaoyu Luo; Shirong Gong; Boyang Shen (Building and Environment, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Decadal transport of trace elements in a cave system based on 16 years monitoring data: Implications for paleoclimate reconstruction - Xin Fu; Yan Yang; Jingyao Zhao; Yidong Li; Xiaomin Chen; Zhimao Ye; Mingyang Li; Jingfeng Lin; Yanzhi Xu (Applied Geochemistry, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Fabrication of self-supporting hierarchical porous metallic glass for pH-universal hydrogen evolution reaction - Xingran Zhao; Junsheng Liu; Heting Zhang; Jihan Jiang; Jiaqing Lin; Jianan Fu; Yu Zhang; Xin Li; Wenqing Ruan; Jiang Ma (Chemical Engineering Journal, 2025)

Chitosan Nano-Selenium Supplementation Improves Production Performance, Egg Quality, and Selenium Deposition in Aging Laying Hens - Gang Shu; Xin Yi; Lei Yang; Jingyi Chen; Kang Fu; Haohuan Li; Funeng Xu; Wei Zhang; Hualing Fu; Bo Jing; Felix Kwame Amevor; Yingjie Wang; et al. (Biological Trace Element Research, 2025)

Sulfonamide-linked π-conjugated carbon nitride with enhanced intramolecular carrier generation and transfer for efficient photocatalysis - Jiajun Fu; Si Chen; Xuanhui Lin; Zongrui Li; Zhao Mo; Mingyue Dong; Zhigang Chen; Hui Xu (Journal of Environmental Chemical Engineering, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

In situ multifunctional gel for hormone-immune therapy of ovarian cancer and prevention of postoperative adhesion - Yankun Zhang; Yanbin Shi; Hengchang Zang; Xiaogang Zhao; Xianglei Fu; Shengnan Qiu; Yuan Zhang; Yingying Liu; Xiaoyu Wan; Zengmei Li; Yaqi Li; Jiamin Zhou; et al. (Chemical Engineering Journal, 2025)

SlRGLG2-SlBEL2 module regulates drought tolerance in tomato - Xiao-Lin Niu; Gang-Shuai Liu; Xiaodan Zhao; Da-Qi Fu (Plant Molecular Biology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Dabrafenib upregulates hypoglycosylated MUC1 and improves the therapeutic efficacy of Tn-MUC1 CAR-T cells - Ziwei Zhou; Yinghua Zhu; Jianli Zhao; Yiming Zhao; Wenkui Fu; Chao Zhou; Jinfang Hu; Yewen Zeng; Yiguang Lin; Hong An; Haibin Yin; Herui Yao; et al. (Science Bulletin, 2025)

Pumpkin seed protein-based hydrogel as gelatin mimics and edible inks in 3D-Printed food - Yan Kong; Shiqi Lin; Siyu Chen; Linzhi Jing; Zhao Liu; Mingyi Wu; Xiaojian Yu; Caili Fu; Jin Wang; Dejian Huang (Food Hydrocolloids, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Effects of Fe/Mg-modified lignocellulosic biochar on in vitro ruminal microorganism fermentation of corn stover - Yuping Liu; Jiyu Sun; Taotao Zhao; Lin Wang; Chenyu Zhao; Jingjing Fu; Dawei Li; Haiye Yu (Bioresource Technology, 2025)

Enhanced remediation of cadmium-contaminated farmland by smooth vetch (Vicia villosa var.) coupled with phosphorus/sulfur co-doped biochar: Synergetic performance and mechanism - Fuxuan Bi; Zhao Jiang; Mengning Wang; Qiutong Lin; Xiaoyang Liu; Libo Fu; Hongli Fan; Weidong Cao; Jianhua Qu; Ying Zhang (Journal of Cleaner Production, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Sea buckthorn polyphenols on gastrointestinal health and the interactions with gut microbiota - Hexi Yuan; Hao Huang; Yinglin Du; Jiaqi Zhao; Shiyang Yu; Yanhong Lin; Yan Chen; Chunhui Shan; Yue Zhao; Tarun Belwal; Xizhe Fu (Food Chemistry, 2025)

Non thermoplastic 3D molding based on coordination crosslinking for on-demand customization carboxymethyl chitosan-based packaging bags - Yongfu Deng; Shuwen Luo; Wenxin Zhao; Fuxiang Wei; Chuanhui Xu; Lihua Fu; Baofeng Lin (Food Packaging and Shelf Life, 2025)

Effect of oral Mn-based nanozymes Mn3O4 NPs on morphological, antioxidation, mucosa, and fecal microbial community in mice colons - Baoyue Zhang; Lei Yang; Zhengkun Wu; Xianxiang Wang; Xiaoling Zhao; Wei Zhang; Danqin Li; Hualin Fu; Juchun Lin; Funeng Xu; Xiaoyang Ai; Gang Shu (Food and Chemical Toxicology, 2025)

Glycolysis of waste polyurethane foam for preparing recycled polymer materials: Optimization and techno-economic evaluation - Chun Chang; Youfeng Jiang; Yucheng Lin; Kai Fu; Chunbao Xu; Shiqiang Zhao (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Impact of oil phase volume fraction on the characteristics of w/o/w emulsions stabilized with alkali-heat-treated rice residue glutelin - Zhixiao Wang; Yuanbo Guo; Xiangjin Fu; Jianan Zhang; Qinlu Lin; Zhao Long; Weidan Guo (Food Research International, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

A large-scale FireLine global positioning method based on a single unmanned aerial vehicle - Yifan Fu; Haiyu Zhang; Xingdong Li; Chuanying Lin; Yue Ma; Hongyang Zhao; Shufa Sun (International Journal of Remote Sensing, 2025)

A simple and colorimetric method utilizing cell-free toehold switch sensors for the detection of Chlamydia trachomatis, Ureaplasma urealyticum and Neisseria gonorrhoeae - Fengling Fang; Hongyan Guo; Zhaopei Guo; Lin Lin; Lu Lai; Yue Shi; Weiquan You; Shanjian Chen; Can Liu; Mingming Zhao; Shaobin Guo; Qishui Ou; et al. (Analytica Chimica Acta, 2025)

Genesis of Botryococcus-rich laminae of the Eocene Upper Xiaganchaigou Formation in the western Qaidam Basin, NW China - Guolong Liu; Mingzhen Zhang; Rongchang Zhao; Dunzhu Jiaoba; Xiangtong Lei; Baoxia Du; Jing Zhang; Shaohua Lin; Peihong Jin; Aijing Li; Jing Peng; Yiqiao Fu; et al. (Marine and Petroleum Geology, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

Experimental study on pressure drop and ice blockage characteristics of ice slurry flow in big-diameter pipes - Bo Yang; Daoke Tang; Weixing Yuan; Xiling Zhao; Lin Fu (International Journal of Refrigeration, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Clinical efficacy and safety of vortioxetine as an adjuvant drug for patients with bipolar depression - Chunxiao Dai; Yaoyang Fu; Xuanwei Li; Meihua Lin; Yinbo Li; Xiao Li; Keke Huang; Chengcheng Zhou; Jian Xie; Qingwei Zhao; Shaohua Hu (Journal of Zhejiang University-SCIENCE B, 2025)

Clock bias prediction of navigation satellite based on BWO-CNN-BiGRU-attention model - Wenlong Sun; Jinping Chen; Caibo Hu; Yongxin Lin; Maolei Wang; He Zhao; Run Zhao; Guitao Fu; Tan Zhao (GPS Solutions, 2025)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Emerging developments and applications of Zr-fumarate MOF membranes for sustainable environmental separations - Mao Fu; Chuanhui Chen; Shuai Zhang; Yuhua You; Huifang Zhao; Bin Lin; Shi-Qiang Wang; Yingchao Dong (Chemical Engineering Journal, 2024)

Emerging nanoradiosensitizers and nanoradioprotectants for enhanced cancer theranostics - Lin Zhao; Yang Sun; Qinrui Fu; Wenjing Xiao (Chemical Engineering Journal, 2024)

Sensitivity Assessment on Satellite Remote Sensing Estimates of Primary Productivity in Shelf Seas - Xiaolong Zhao; Jianan Sun; Qingjun Fu; Xiao Yan; Lei Lin (Journal of Marine Science and Engineering, 2024)
The vertically generalized production model (VGPM) is one of the most important methods for estimating marine net primary productivity (PP) using remote sensing. However, different data sources and parameterization schemes of the input variables for the VGPM can introduce uncertainties to the model results. This study compared the PP results from different data sources and parameterization schemes of three major input variables (i.e., chlorophyll-a concentration (Copt), euphotic depth (Zeu), and maximum photosynthetic rate (PoptB)) and evaluated the sensitivity of VGPM in the Yellow and Bohai Seas on the inputs. The results showed that the sensitivity in the annual mean PP was approximately 40%. Seasonally, the sensitivity was lowest in the spring (35%), highest in the winter (70%), and approximately 60% in the summer and autumn. Spatially, the sensitivity in nearshore water (water depth

Black biodegradable mulching increases grain yield and net return while decreasing carbon footprint in rain-fed conditions of the Loess Plateau - Nanping Lin; Xiaoqi Luo; Jiaxuan Wen; Jiankang Fu; Haolei Zhang; Kadambot H.M. Siddique; Hao Feng; Ying Zhao (Field Crops Research, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Correction to: Identification and map‑based cloning of an EMS‑induced mutation in wheat gene TaSP1 related to spike architecture - Lin Zhang; Huidan Zhou; Xian Fu; Niuniu Zhou; Mengjie Liu; Shenglong Bai; Xinpeng Zhao; Ruiru Cheng; Suoping Li; Dale Zhang (Theoretical and Applied Genetics, 2024)

Anthropogenic shrub encroachment has accelerated the degradation of desert steppe soil over the past four decades - Yanan Zhao; Hongmei Wang; Zhigang Li; Gang Lin; Jingying Fu; Zhili Li; Zhenjie Zhang; Dong Jiang (Science of The Total Environment, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Characterization and immune role of class B scavenger receptor member 1 in spotted sea bass (Lateolabrax maculatus) - Yichen Fu; Chao Zhao; Changhong Lin; Bo Zhang; Lulu Yan; Bo Zhang; Pengfei Wang; Lihua Qiu (Fish & Shellfish Immunology, 2024)

Synergistic strategy via modulated energy filtering and hierarchical defects evolution for high performance GeTe thermoelectrics - Ge Fu; Shangchao Lin; Yixuan Liu; Jie Xiao; Changying Zhao (Chemical Engineering Journal, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

Utilizing spontaneous plants for sustainable development in residential green spaces: Insights from environmental drivers and niche analysis in Fuzhou City, China - Chengyu Ran; Junyi Pan; Yuxin Lin; Tongyan Li; Yaling Huang; Jingkai Huang; Shiyuan Fan; Wenqiang Fang; Shuang Zhao; Yuxiang Liu; Jiali Jin; Weicong Fu (Journal of Environmental Management, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

The role of a novel secretory peptidoglycan recognition protein with antibacterial ability from the Chinese Oak Silkworm Antheraea pernyi in humoral immunity - Xutong Duan; Ting Fu; Chang Liu; Fuhui Wang; Chengbao Liu; Lin Zhao; JinZhu Yu; Xialu Wang; Rong Zhang (Insect Biochemistry and Molecular Biology, 2024)

Long-range infrared absorption spectroscopy and fast mass spectrometry for rapid online measurements of volatile organic compounds from black tea fermentation - Chongshan Yang; Leizi Jiao; Chunwang Dong; Xuelin Wen; Peng Lin; Dandan Duan; Guanglin Li; Chunjiang Zhao; Xinglan Fu; Daming Dong (Food Chemistry, 2024)

Ultrathin-flexible multifunctional MXene composite hydrogels with good mechanical properties-high strain sensitivity and ultra-broadband EMI shielding performances - Wenchong Ouyang; Lin Mei; Qi Liu; Chengbiao Ding; Yanming Liu; Chengwei Zhao; Limin Xu; Fu Lu; Dongpeng Luo; Chunguang Miao; Yu Bai; Quanming Lu; et al. (Chemical Engineering Journal, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Bacterial assembly and succession patterns in conventional and advanced drinking water systems: From source to tap - Jie Liu; Renxin Zhao; Jie Feng; Wenjie Fu; Lijia Cao; Jiayu Zhang; Yusha Lei; Jiajin Liang; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2024)

Benzo[a]pyrene evokes epithelial-mesenchymal transition and pulmonary fibrosis through AhR-mediated Nrf2-p62 signaling - Meng-Die Li; Li-Hong Chen; Hui-Xian Xiang; Ya-Lin Jiang; Bian-Bian Lv; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Composting of invasive plants in urban watercourses and its application in riverbanks: mechanisms and compost quality assessment - Peiyin Wang; Guiping Fu; Zhipeng Guo; Lin Zhao; Weicheng Pang; Chao Pan; Ke Wang; Qiqi Wu; Yurou Chen (Journal of Soils and Sediments, 2024)

Pretreatment of wastepaper with an aqueous solution of amino acid-derived ionic liquid for biochar production as adsorbent - Yi Jia; Shuai Nian; Wenxia Zhao; Lin Fu; Xiaokai Zhang; Ian Beadham; Shuchang Zhao; Changbo Zhang; Yun Deng (Journal of Environmental Management, 2024)

Identification and map-based cloning of an EMS-induced mutation in wheat gene TaSP1 related to spike architecture - Lin Zhang; Huidan Zhou; Xian Fu; Niuniu Zhou; Mengjie Liu; Shenglong Bai; Xinpeng Zhao; Ruiru Cheng; Suoping Li; Dale Zhang (Theoretical and Applied Genetics, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Characteristics of sub-micron aerosols above the urban canopy in Beijing during warm seasons - Qingqing Wang; Wei Du; Wei Zhou; Yingjie Zhang; Conghui Xie; Jian Zhao; Weiqi Xu; Guiqian Tang; Pingqing Fu; Zifa Wang; Yele Sun; Lin Peng (Science of The Total Environment, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

BMSCs-laden mechanically reinforced bioactive sodium alginate composite hydrogel microspheres for minimally invasive bone repair - Shengjie Jiang; Hua Jing; Yu Zhuang; Jinjie Cui; Zeyu Fu; Dejian Li; Cancan Zhao; Usman Liaqat; Kaili Lin (Carbohydrate Polymers, 2024)

CFD simulation of pumping ventilation with two asymmetrically arranged openings on the rear wall in a three-story isolated building - Huai-Yu Zhong; Jie Sun; Chao Lin; Hideki Kikumoto; Wei Dong; Yang Cai; Fu-Yun Zhao; Song-Heng Wu; Fu-Ping Qian (Building and Environment, 2024)

MAPK/NF-κB signaling mediates atrazine-induced cardiorenal syndrome and antagonism of lycopene - Fu-Wei Jiang; Jian-Ying Guo; Jia Lin; Shi-Yong Zhu; Xue-Yan Dai; Muhammad Asmat Ullah Saleem; Yi Zhao; Jin-Long Li (Science of The Total Environment, 2024)

A vertical-flow constructed wetland–microalgal membrane photobioreactor integrated system for treating high-pollution-load marine aquaculture wastewater: A lab-scale study - Lin Zhao; Jun Tang; Yuwei Xu; Yifan Zhang; Zihao Song; Guiping Fu; Zhangli Hu (Science of The Total Environment, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Occurrence of Cladosporium herbarum causing leaf spot on Avena sativa in China - Jiangui Zhang; Guiqin Zhao; Jikuan Chai; Liang Zeng; Wenlong Gong; Fu Ran; Xiumei Nie; Ruifang Zhang; Doudou Lin (Crop Protection, 2024)

Ferrostatin‑1 alleviates liver injury via decreasing ferroptosis following ricin toxin poisoning in rat - Ruijiao Lin; Zijie Jia; Hongbing Chen; Hongli Xiong; Cunhao Bian; Xin He; Bi Wei; Junfeng Fu; Minzhu Zhao; Jianbo Li (Toxicology, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Flutter control optimization for a 5000 m suspension bridge with active aerodynamic flaps: a CFD-enabled strategy - Zilong Wang; Lin Zhao; Yiheng Fu; Genshen Fang; Wei Cui; Ke Li; Yaojun Ge (Engineering Structures, 2024)

Numerical simulation method and deterioration analysis of load-bearing performance of tunnel linings containing cold joints in plain concrete - Huang-Shi Deng; He-Lin Fu; Yi-Min Wu; Yi-Bo Zhao; Hai-Dong Yi (Tunnelling and Underground Space Technology, 2024)

An intrusion and environmental effects of man-made silver nanoparticles in cold seeps - Kelei Zhu; Jiawei Liu; Mingyu Zhao; Lulu Fu; Zengfeng Du; Fanqi Meng; Lin Gu; Peiyu Liu; Yan Liu; Chaoqun Zhang; Xin Zhang; Jinhua Li (Science of The Total Environment, 2024)

Vitamin D3 activates the innate immune response and xenophagy against Nocardia seriolae through the VD receptor in liver of largemouth bass (Micropterus salmoides) - Quanquan Cao; Ju Zhao; Mingyao Yan; Zhong Luo; Fu Luo; Lin Feng; Weidan Jiang; Pei Wu; Yan Wang; Debin Li; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

Synthesis and application of wetland plant-based functional materials for aqueous antibiotics removal - Tao Fu; Linna Du; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Yejian Zhang; Chunzhen Fan; Wen Wang; Fuyuan Ran; Ping Lin; Chunjie Zhong (Science of The Total Environment, 2024)

Permafrost on the Tibetan Plateau is degrading: Historical and projected trends - Tongqing Shen; Peng Jiang; Qin Ju; Jiahui Zhao; Xuegao Chen; Hui Lin; Bin Yang; Changhai Tan; Ying Zhang; Xinting Fu; Zhongbo Yu (Journal of Hydrology, 2024)

Removal of multiple pollutants in air pollution control devices of a coal-fired boiler installed with a flue gas condensation scrubber - Tailin Chen; Lejun Deng; Yuzhong Li; Jingwei Li; Xiling Zhao; Lin Fu (Journal of Cleaner Production, 2024)

Mechanical-Effect descriptor for oxygen reduction reaction and hydrogen evolution reaction on Single-Atomic Ni-Graphene catalysts - Wei Zhang; Fu-li Sun; Xue-long Zhang; Shuang-te Zhao; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2024)

4-Hydroxybenzenesulfonic acid triggers rapid preparation of phenolic aerogel composites by ambient pressure drying - Xi Zhao; Lin Chen; Peng-Gang Su; Lin-Xi Xiao; Hai-Bo Zhao; Teng Fu; Xiu-Li Wang; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Metabolic engineering of Paenibacillus polymyxa for effective production of 2,3-butanediol from poplar hydrolysate - Jikun Zhang; Jianzhi Zhao; Quanbin Fu; Haiyang Liu; Min Li; Zhongyue Wang; Wei Gu; Xueming Zhu; Rongshan Lin; Li Dai; Kai Liu; Chengqiang Wang (Bioresource Technology, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Characterization of the aerosol vertical distributions and their impacts on warm clouds based on multi-year ARM observations - Yun Lin; Yoshihide Takano; Yu Gu; Yuan Wang; Shujun Zhou; Tianhao Zhang; Kuilin Zhu; Jingyu Wang; Bin Zhao; Gang Chen; Damao Zhang; Rong Fu; et al. (Science of The Total Environment, 2023)

Comparison of the environmental impact of typical packaging systems for food cold chain express based on life cycle assessment - Teng Meng; Yinpu Wang; Lin Fu; Yuelin Wang; Na Zhang; Zhao Wang; Qi Yang (Journal of Cleaner Production, 2023)

Responses of bird communities to riparian park habitat factors: a case study in a highly urbanized area of Fuzhou city, China - Dulai Zheng; Peilin Huang; Weizhen Xu; Ziluo Huang; YuJie Zhao; Yinghong Ding; Yuxin Lin; Ruoxian Zheng; Zhipeng Zhu; Ziru Chen; Weicong Fu (Environment, Development and Sustainability, 2023)

Differentiating environmental scenarios to establish geochemical baseline values for heavy metals in soil: A case study of Hainan Island, China - Yanling Sun; Jianzhou Yang; Kai Li; Jingjing Gong; Jianweng Gao; Zhenliang Wang; Yongwen Cai; Keqiang Zhao; Shuqi Hu; Yangang Fu; Zhuang Duan; Lujun Lin (Science of The Total Environment, 2023)

Scene-aware refinement network for unsupervised monocular depth estimation in ultra-low altitude oblique photography of UAV - Kailong Yu; Hao Li; Linjie Xing; Tao Wen; Die Fu; Yang Yang; Chengjiang Zhou; Rong Chang; Shan Zhao; Lin Xing; Haicheng Bai (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

Multistage plate subduction controls intraplate volcanism and cratonic lithospheric thinning in Northeast Asia - Zhi Wang; Lijun Liu; Yi Fu; Liang Zhao; Jian Lin; Zhenmin Jin; Bo Zheng (Earth-Science Reviews, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Effects of different aeration strategies and ammonia-nitrogen loads on nitrification performance and microbial community succession of mangrove constructed wetlands for saline wastewater treatment - Lin Zhao; Guiping Fu; Anzu Zeng; Bingzhen Cheng; Zihao Song; Zhangli Hu (Chemosphere, 2023)

Coupling the digital twin technology and life cycle assessment: Carbon dioxide emissions from polysilicon production - Shengqiang Yang; Zhiqiang Yu; Wenhui Ma; Lin Ma; Chaochun Li; Ling Fu; Ming Li; Zewen Zhao; Yuchen Yang (Sustainable Production and Consumption, 2023)

Asymmetric wettable three-dimensional Janus all-cellulose aerogel: Controllable construction with a similar phase self-assembling strategy and oil-water separation performance - Jingjing Zhang; Congcong Wang; Zhibo Lin; Qian Fu; Chenxi Niu; Zaowen Zhao; Lingbin Lu (Journal of Environmental Chemical Engineering, 2023)

Citric acid enhanced oxytetracycline degradation by Fe(Ⅲ)/peracetic acid: Performance, mechanism and influence factors - Yiqing Liu; Lin Tian; Zhenran Wang; Yongsheng Fu; Dandan Zhao (Journal of Environmental Chemical Engineering, 2023)

Impact of COVID-19 pandemic on profiles of antibiotic-resistant genes and bacteria in hospital wastewater - Liang Zhao; Ziquan Lv; Liangqiang Lin; Xiaowei Li; Jian Xu; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Pollution, 2023)

Phase-modulated built-in electric field to boost photogenerated electron migration for efficient dehalogenation - Meng Ren; Pengjie Zhao; Xinping Fu; Meng Liu; Yuting Ning; Yinjie Zhang; Chunyan Wang; Aijun Lin; Jun Cui (Chemical Engineering Journal, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Host-specific bacterial communities associated with six cold-seep sponge species in the South China Sea - Yan Wang; Lin Gong; Zhaoming Gao; Yong Wang; Feng Zhao; Lulu Fu; Xinzheng Li (Frontiers in Marine Science, 2023)
The cold-seep sponge holobionts are attracting growing attention in recent years. In this study, we utilized 16S rRNA amplicons to characterize the bacterial communities of six deep-sea sponge species found in sponge grounds at the Formosa Ridge cold seep in the South China Sea. Bacterial communities in these geographically proximal sponge species are dominated by Proteobacteria (mainly Gammaproteobacteria and Alphaproteobacteria) but exhibit distinct diversity and compositions among communities. Further analysis revealed that the SUP05 clade (Thioglobaceae) dominated most of the sponge samples. Meanwhile, phylogenetic analysis showed that the six sponge species harbored diverse SUP05 OTU phylotypes, indicating significant divergence within this clade. Additionally, operational taxonomic units (OTUs) of the family Methylomonadaceae, another abundant group in these sponges, displayed a significant genetic distance both from each other and from known species. Our findings support the hypothesis of the host-species specificity of sponge-associated bacterial communities, a widely accepted concept in shallow-water and other deep-sea sponges. The presence of dominant functional microbes, such as sulfur- and methanol-oxidizing bacteria, suggests their crucial role as chemosynthetic symbionts in facilitating the niche adaption of sponge hosts to the cold seep ecosystem. In conclusion, our study reveals the diverse and novel bacterial communities in deep-sea sponges from cold seep environments, contributing new knowledge to the host-species specificity of bacterial communities within sponges and highlighting the potential significance of functional microbes in cold seep ecosystems with dynamic energy supplies.

Tiliroside induces ferroptosis to repress the development of triple-negative breast cancer cells - Chuang Hu; Jian-Fu Zhao; Yi-Ming Wang; Xian-lin Wu; Ling Ye (Tissue and Cell, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Hepatotoxicity screening and ranking of structurally different pyrrolizidine alkaloids in zebrafish - Yueyang Pan; Jiang Ma; Hui Zhao; Peter P. Fu; Ge Lin (Food and Chemical Toxicology, 2023)

GS6.1 controls kernel size and plant architecture in rice - Hongyuan Zhao; Yu Fu; Guiquan Zhang; Yingqin Luo; Weifeng Yang; Xiaoya Liang; Lin Yin; Zhenwu Zheng; Yijun Wang; Zhan Li; Haitao Zhu; Jinyan Huang; et al. (Planta, 2023)

Lead-imprinted polyvinylidene fluoride membrane for selective removal of lead from contaminated water: material fabrication, filtration application, and mechanism study - Dandan Zhao; Chen Fu; Sudan Lin; Yongzhi Xu; Haoran He; Siyuan Liu; Xueqing Shi (Environmental Science and Pollution Research, 2023)

Microecological health assessment of water environment and sediment based on metagenomics: a case study of Guixi River in Chongqing, China - Xia Su; Fu-qing Xu; Shang-jie Chen; Fang Gou; Yun-chun Shi; Zhi-lin Xing; Ren-qing Peng; Ying-ying Deng; Ten Zhang; Juan Xiong; Tian-tao Zhao (Environmental Monitoring and Assessment, 2023)

Joint semantic–geometric learning for polygonal building segmentation from high-resolution remote sensing images - Weijia Li; Wenqian Zhao; Jinhua Yu; Juepeng Zheng; Conghui He; Haohuan Fu; Dahua Lin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Relating critical and limiting fluxes to metastable and long-term stable fluxes in colloidal membrane filtration through collision-attachment theory - Junxia Liu; Wei Fu; Xuri Yu; Haiyan Yang; Dongsheng Zhao; Zhihong Wang; Lin Wang; Xianhui Li; Chuyang Y. Tang (Water Research, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Novel Y2O3 based calcium-alginate beads for highly selective adsorption of phosphate from aqueous solution - Sudan Lin; Yongzhi Xu; Chen Fu; Haifeng Zhang; Qiaoping Kong; Haoran He; Siyuan Liu; Xueqing Shi; Dandan Zhao (Environmental Science and Pollution Research, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Taurine reduces apoptosis mediated by endoplasmic reticulum stress in islet β-cells induced by high-fat and -glucose diets - Dongdong Zhao; Xiaozhou Zhang; Yongxin Bian; Lu Meng; Yutong Wu; Yidi Ma; Chen Li; Jingjing Wang; Zizheng Fu; Jingyuan Dai; Deqi Yin; Shumei Lin; et al. (Food and Chemical Toxicology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Paraburkholderia sp. GD17 improves tomato plant growth and resistance to Botrytis cinerea-induced disease - Anqi Gu; Danni Zhao; Huaqiang Liu; Wei Fu; Guangzhe Li; Lin Hao (Plant and Soil, 2023)

Triassic granitoids in the East Kunlun Orogenic Belt, Northwestern China: magmatic source and implications for geodynamic evolution - Zhi-He Xu; Wei Xin; Xiao-Dong Zhou; Qing-Lin Xu; Fu-Wen Li; Zhao-Jun Song (International Geology Review, 2023)

A novel autotrophic denitrification and nitrification integrated constructed wetland process for marine aquaculture wastewater treatment - Lin Zhao; Guiping Fu; Weicheng Pang; Xiaxin Li; Chao Pan; Zhangli Hu (Chemosphere, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Roles of Histone Acetyltransferases and Deacetylases in the Retinal Development and Diseases - Jingjing Wang; Shuyu Feng; Qian Zhang; Huan Qin; Chunxiu Xu; Xuefei Fu; Lin Yan; Yaqin Zhao; Kai Yao (Molecular Neurobiology, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Plant identity shapes phyllosphere microbiome structure and abundance of genes involved in nutrient cycling - Jian Li; Ming-Kang Jin; Roy Neilson; Shi-Lin Hu; Yi-Jia Tang; Zhao Zhang; Fu-Yi Huang; Jing Zhang; Xiao-Ru Yang (Science of The Total Environment, 2023)

Co-hydrothermal carbonization of polyvinyl chloride and lignocellulose biomasses for chlorine and inorganics removal - Jing Zhang; Yuhan Chen; Xu Xia; Binbin Fu; Chuanjin Lin; Guangchao Jia; Xin Cui; Fang Liu; Peitao Zhao; Yimin Li (Waste Management, 2023)

A new strategy: Inhibitory effect and mechanism of Cymbopogon martinii essential oil on Aspergillus flavus - Lizhen Lin; Shuaipeng Chen; Wenxin Xia; Tingting Li; Lin Dong; Yan Zhang; Yuanyuan Zhang; Hangying Li; Yunsheng Zhao; Xueyan Fu (Food Bioscience, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Enhancement of lycopene bioaccessibility in tomatoes using excipient emulsions: Effect of dark tea polysaccharides - Chao Wang; Yinxin Fu; Yi Cao; Jialu Huang; Hongyi Lin; Peiyi Shen; David Julian McClements; Lingyu Han; Tiantian Zhao; Xiaoxuan Yan; Qian Li (Food Research International, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

A histological study of vascular wall resident stem cells in venous malformations - Hou-Fu Xia; Wen-Qiang Lai; Gao-Hong Chen; Ye Li; Qi-Hui Xie; Yu-Lin Jia; Gang Chen; Yi-Fang Zhao (Cell and Tissue Research, 2022)

Horizontal and vertical heterogeneity of sediment microbial community in Site F cold seep, the South China Sea - Xinyi Zhai; Xiaochong Shi; Haojin Cheng; Peng Yao; Bin Zhao; Lin Chen; Jiwen Liu; Lei Cao; Minxiao Wang; Lulu Fu; Xiao-Hua Zhang; Min Yu (Frontiers in Marine Science, 2022)
Site F is the most vigorous cold seep known on the continental slope of the northern South China Sea. Up to now, the microbial community structures in sediments of Site F based on the high-throughput sequencing of the 16S rRNA genes have been studied extensively. However, few studies investigated the microbial community structures at fine vertical scales of Site F and control stations outside Site F. In this study, a comprehensive investigation of microbial communities in sediments of Site F along the depths varying from 0 to 24 cm below sea floor (cmbsf) of four sampling sites—SRS (Southern Reduced Sediment), NRS (Northern Reduced Sediment), Control 1 (close to Site F), and Control 2 (far from Site F)—was carried out. The high relative abundances of anaerobic methanotrophic archaea (ANME), Desulfobacterota [sulfate-reducing bacteria (SRB)], and Campylobacteria [sulfur-oxidizing bacteria (SOB)] in SRS and NRS indicated that these two sites were newborn cold seep sites compared with non-seep sites, Control 1, and Control 2. A positive correlation between ANME-1b, ANME-2, and SEEP-SRB and an enrichment of Sulfurovum and Methlomonadaceae were found in the surface sediments of both SRS and NRS, indicating that the processes of anaerobic oxidation of methane (AOM), sulfur oxidation, and sulfate reduction might occur in seep sites. SRS was enriched with ANME-1b and SEEP-SRB2 with a proposed sulfate-methane transition zone (SMTZ) approximately located at 8 cmbsf. The high abundance of ANME in SRS may due to the high concentration of methane. NRS was enriched with ANME-2, Desulfatiglans , Sulfurovum , and Methanosarcinaceae with a proposed SMTZ at about 10 cmbsf. According to the analyses of microbial community structure and environmental factors, NRS could be described as a notable cold seep reduced sediment site with low sulfate and high H 2 S that nourished abundant SEEP-SRB1, ANME-2, Methanosarcinales , and Sulfurovum , which showed similar distribution pattern. Our study expands the current knowledge on the differences of microbial communities in cold seep sites and non-seep sites and sheds light on the horizontal and vertical heterogeneity of sediment microbial community in Site F.

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Identification and validation of suitable reference genes for quantitative real-time PCR studies in Adiantum reniforme var. sinense - Qi Fu; Lin Xiang; Kai-ge Zhao; Long-qing Chen (Journal of Plant Biochemistry and Biotechnology, 2022)

Endothelial cells induce degradation of ECM through enhanced secretion of MMP14 carried on extracellular vesicles in venous malformation - Gao-Hong Chen; Jie-Gang Yang; Hou-Fu Xia; Lin-Zhou Zhang; Yin-Hsueh Chen; Kui-Ming Wang; Xu Duan; Lian-Zhi Wu; Yi-Fang Zhao; Gang Chen (Cell and Tissue Research, 2022)

Correction to: Inhibition of Dectin-1 Ameliorates Neuroinflammation by Regulating Microglia/Macrophage Phenotype After Intracerebral Hemorrhage in Mice - Xiongjie Fu; Hanhai Zeng; Jikuang Zhao; Guoyang Zhou; Hang Zhou; Jianfeng Zhuang; Chaoran Xu; Jianru Li; Yucong Peng; Yang Cao; Yin Li; Huaijun Chen; et al. (Translational Stroke Research, 2022)

Extraction, purification, bioactivity and pharmacological effects of capsaicin: a review - Fengzhang Wang; Yong Xue; Lin Fu; Yongtao Wang; Minxia He; Liang Zhao; Xiaojun Liao (Critical Reviews in Food Science and Nutrition, 2022)

Diminished miR-374c-5p negatively regulates IL (interleukin)-6 in unexplained recurrent spontaneous abortion - Lin Zhao; Li Han; Guozhen Hei; Ran Wei; Zhen Zhang; Xiaoxiao Zhu; Qiang Guo; Chu Chu; Xiaoxiao Fu; Ke Xu; Xia Li (Journal of Molecular Medicine, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Comparison of the Macrozoobenthic Community and Sedimentary Environment with and Without Horseshoe Crab Presence in the Crocodile Island Intertidal Zone, Xiamen, China - Lizhe Cai; Xiaoyu Zhao; Wenqing Peng; Jingxiang Lin; Deyuan Yang; Yiyong Rao; Sujing Fu; Xinwei Chen; Wenzhi Cao (Journal of Ocean University of China, 2022)

Associations of air pollutants with pneumonia hospital admissions in Qingdao, China: a prospective cohort study - Hai-Tao Wang; Hong Zhang; Fu-Zhong Xue; Lin Zhao; Wu-Chun Cao (Environmental Science and Pollution Research, 2022)

Genome-wide analysis of BURP genes and identification of a BURP-V gene RcBURP4 in Rosa chinensis - Lufeng Fu; Zhujun Zhang; Hai Wang; Xiaojuan Zhao; Lin Su; Lifang Geng; Yizeng Lu; Boqiang Tong; Qinghua Liu; Xinqiang Jiang (Plant Cell Reports, 2022)

Phactr1 negatively regulates bone mass by inhibiting osteogenesis and promoting adipogenesis of BMSCs via RhoA/ROCK2 - Wei Lin; Zhipeng Chen; Xiaoyi Mo; Shengli Zhao; Zhenxing Wen; Wing Hoi Cheung; Dan Fu; Bailing Chen (Journal of Molecular Histology, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Inhibition of Dectin-1 Ameliorates Neuroinflammation by Regulating Microglia/Macrophage Phenotype After Intracerebral Hemorrhage in Mice - Xiongjie Fu; Hanhai Zeng; Jikuang Zhao; Guoyang Zhou; Hang Zhou; Jianfeng Zhuang; Chaoran Xu; Jianru Li; Yucong Peng; Yang Cao; Yin Li; Huaijun Chen; et al. (Translational Stroke Research, 2021)

Analysis of the thaumatin-like genes of Rosa chinensis and functional analysis of the role of RcTLP6 in salt stress tolerance - Lin Su; Xiaojuan Zhao; Lifang Geng; Lufeng Fu; Yizeng Lu; Qinghua Liu; Xinqiang Jiang (Planta, 2021)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

Isolation and evaluation of the biocontrol potential of Talaromyces spp. against rice sheath blight guided by soil microbiome - Aqleem Abbas; Yanping Fu; Zheng Qu; Huizhang Zhao; Yongjian Sun; Yang Lin; Jiatao Xie; Jiasen Cheng; Daohong Jiang (Environmental Microbiology, 2021)
Summary Rice sheath blight caused by Rhizoctonia solani is the major disease of rice that seriously threatens food security worldwide. Efficient and eco‐friendly biological approaches are urgently needed since no resistant cultivars are available. In this study, fallow and paddy soils were initially subjected to microbiome analyses, and the results showed that Talaromyces spp. were significantly more abundant in the paddy soil, while Trichoderma spp. were more abundant in the fallow soil, suggesting that Talaromyces spp. could live and survive better in the paddy soil. Five Talaromyces isolates, namely, TF‐04, TF‐03, TF‐02, TF‐01 and TA‐02, were isolated from the paddy soil using sclerotia of R . solani as baits and were further evaluated for their activity against rice sheath blight. These isolates efficiently parasitized the hyphae and rotted the sclerotia even at higher water contents in the sterilized sand and the soil. Isolate TF‐04 significantly promoted rice growth, reduced the severity of rice sheath blight and increased the rice yield under outdoor conditions. Defence‐related genes were upregulated and enzyme activities were enhanced in rice treated with isolate TF‐04. Our research supplies a microbiome‐guided approach to screen biological control agents and provides Talaromyces isolates to biologically control rice sheath blight.

Engrafted primary type-2 astrocytes improve the recovery of the nigrostriatal pathway in a rat model of Parkinson's disease - Yanyun Sun; Xiao-jun Lu; Xinghui Fu; Ye Zhang; Yan Zhan; Jiabing Liu; Lingxia Zhao; Chun-lin Xia (Molecular and Cellular Biochemistry, 2021)

Porous Cd0.5Zn0.5S nanocages derived from ZIF-8: boosted photocatalytic performances under LED-visible light - Lin Wu; Huifen Fu; Qi Wei; Qian Zhao; Peng Wang; Chong-Chen Wang (Environmental Science and Pollution Research, 2021)

Cold water anomalies in the middle layer of the northern Taiwan Strait in spring—a numerical approach - Zhonghua Zhao; Jianwei Lin; Jun Fu; Yuwu Jiang (Ocean Dynamics, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Increased EZH2 Levels in Anterior Cingulate Cortex Microglia Aggravate Neuropathic Pain by Inhibiting Autophagy Following Brachial Plexus Avulsion in Rats - Xiang-Lei Meng; Pengfei Fu; Lin Wang; Xun Yang; Guanghui Hong; Xin Zhao; Jie Lao (Neuroscience Bulletin, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Reduction of Human DNA Contamination in Clinical Cerebrospinal Fluid Specimens Improves the Sensitivity of Metagenomic Next-Generation Sequencing - Xin-Chao Ji; Lin-Fu Zhou; Chao-Yang Li; Ya-Jun Shi; Meng-Li Wu; Yun Zhang; Xiao-Fei Fei; Gang Zhao (Journal of Molecular Neuroscience, 2020)

Characterization and bioactive potentials of secondary metabolites from Fusarium chlamydosporum - Zhao-Fu Wang; Wei Zhang; Lin Xiao; Yuan-Ming Zhou; Feng-Yu Du (Natural Product Research, 2020)

Nitrogen fertilizer enhances zinc and cadmium uptake by hyperaccumulator Sedum alfredii Hance - Ziwen Lin; Chunying Dou; Yongfu Li; Hailong Wang; Nabeel Khan Niazi; Shaobo Zhang; Dan Liu; Keli Zhao; Weijun Fu; Yongchun Li; Zhengqian Ye (Journal of Soils and Sediments, 2020)

Extreme stress threatened double rice production in Southern China during 1981–2010 - Sheng-Li Liu; Xing Wang; Shou-Tian Ma; Xin Zhao; Fu Chen; Xiao-Ping Xiao; Rattan Lal; Hai-Lin Zhang (Theoretical and Applied Climatology, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Evaluation of the integrated multi-satellite retrievals for global precipitation measurement over the Tibetan Plateau - Lu Ma; Lin Zhao; Li-ming Tian; Li-ming Yuan; Yao Xiao; Le-le Zhang; De-fu Zou; Yong-ping Qiao (Journal of Mountain Science, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

ATMT transformation efficiencies with native promoters in Botryosphaeria kuwatsukai causing ring rot disease in pear - Xueying Gu; Jiamin Zhao; Hongkai Wang; Fu-Cheng Lin; Qingyuan Guo; Neeraj Shrivastava; Rajesh Jeewon (World Journal of Microbiology and Biotechnology, 2018)

Full-length and defective enterovirus G genomes with distinct torovirus protease insertions are highly prevalent on a Chinese pig farm - Yan Wang; Wen Zhang; Zhijian Liu; Xingli Fu; Jiaqi Yuan; Jieji Zhao; Yuan Lin; Quan Shen; Xiaochun Wang; Xutao Deng; Eric Delwart; Tongling Shan; et al. (Archives of Virology, 2018)

Estrogen deficiency compromised the β2AR-Gs/Gi coupling: implications for arrhythmia and cardiac injury - Hongjian Hou; Zhiwei Zhao; Jeremiah Ong’achwa Machuki; Lin Zhang; Yan Zhang; Lu Fu; Jinxia Wu; Yuyu Liu; Sian E. Harding; Hong Sun (Pflügers Archiv - European Journal of Physiology, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

C5a/C5aR Pathway Plays a Vital Role in Brain Inflammatory Injury via Initiating Fgl-2 in Intracerebral Hemorrhage - Bangqing Yuan; Fenlan Fu; Shaokuan Huang; Chuangan Lin; Guang Yang; Kunlong Ma; Hui Shi; Zhao Yang (Molecular Neurobiology, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

First discovery of a Palaeoproterozoic A-type granite in southern Wuyishan terrane, Cathaysia Block: evidence from geochronology, geochemistry, and Nd–Hf–O isotopes - Zhi-Hong Chen; Ling Zhao; Dan-Dan Chen; Xi-Lin Zhao; Guang-Fu Xing (International Geology Review, 2017)

A novel trichosanthin fusion protein with increased cytotoxicity to tumor cells - Bing Lin; Xu-Zhong Yang; Xue-Wei Cao; Tao-Zhu Zhang; Fu-Jun Wang; Jian Zhao (Biotechnology Letters, 2017)

N-cadherin regulates beta-catenin signal and its misexpression perturbs commissural axon projection in the developing chicken spinal cord - Ciqing Yang; Xiaoying Li; Congrui Wang; Sulei Fu; Han Li; Zhikun Guo; Shanting Zhao; Juntang Lin (Journal of Molecular Histology, 2016)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Bioethanol production by heterologous expression of two individual 1-FEH genes from Helianthus tuberosus in Saccharomyces cerevisiae 6525 - Xi Zhang; Huanhuan Xu; Ruixin Fu; Lijin Jin; Haiyan Zhao; Lin Wang; Mingxiang Liang (BioEnergy Research, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

Palaeoproterozoic A-type magmatism in northern Wuyishan terrane, Southeast China: petrogenesis and tectonic implications - Zhi-Hong Chen; Guang-Fu Xing; Xi-Lin Zhao (International Geology Review, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Challenges and adaptations of farming to climate change in the North China Plain - Hai-Lin Zhang; Xin Zhao; Xiao-Gang Yin; Sheng-Li Liu; Jian-Fu Xue; Meng Wang; Chao Pu; Rattan Lal; Fu Chen (Climatic Change, 2015)

A new sesquiterpenoid from the rhizomes of Homalomena occulta - Jie Zhao; Jiao Wu; Fu-lin Yan (Natural Product Research, 2014)

Soil microbial systems respond differentially to tetracycline, sulfamonomethoxine, and ciprofloxacin entering soil under pot experimental conditions alone and in combination - Junwei Ma; Hui Lin; Wanchun Sun; Qiang Wang; Qiaogang Yu; Yuhua Zhao; Jianrong Fu (Environmental Science and Pollution Research, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Spatial structure of eukaryotic ultraplankton community in the northern South China Sea - Zhao-Yu Jiang; You-Shao Wang; Fu-Lin Sun (Biologia, 2014)

Intraneuronal accumulation of Aβ42 induces age-dependent slowing of neuronal transmission in Drosophila - Jing-Ya Lin; Wen-An Wang; Xiao Zhang; Hai-Yan Liu; Xiao-Liang Zhao; Fu-De Huang (Neuroscience Bulletin, 2014)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Biodegradation of bensulfuron-methyl and its effect on bacterial community in paddy soils - Xiao-Yan Lin; Yu-Yi Yang; Yu-Hua Zhao; Qing-Lin Fu (Ecotoxicology, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Computational prediction and experimental assessment of an HLA-A*0201-restricted cytotoxic T lymphocyte epitope from neutral endopeptidase - Jingbo Zhang; Zhengcai Jia; Zhihua Lin; Jingyi Li; Xiaolan Fu; Yunjian Huang; Jinghong Zhao; Ling Nie; Weiping Hou; Fahuan Yuan; Yuzhang Wu (Immunologic Research, 2012)

Physiological response of Cu and Cu mine tailing remediation of Paulownia fortunei (Seem) Hemsl - Zao-Fa Jiang; Su-Zhen Huang; Yu-Lin Han; Jiu-Zhou Zhao; Jia-Jia Fu (Ecotoxicology, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2011)

Dynamic Changes of Heme Oxygenase-1 in the Hippocampus of Rats After Acute Carbon Monoxide Poisoning - Li Guan; Yan-Lin Zhang; Tao Wen; Xi-Fu Wang; Ming-Xia Zhu; Jin-Yuan Zhao (Archives of Environmental Contamination and Toxicology, 2011)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

Chymase induces profibrotic response via transforming growth factor-β1/Smad activation in rat cardiac fibroblasts - Xiao-Yan Zhao; Lian-You Zhao; Qiang-Sun Zheng; Jin-Lin Su; Hao Guan; Fu-Jun Shang; Xiao-Lin Niu; Yan-Ping He; Xiao-Long Lu (Molecular and Cellular Biochemistry, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)

Ground failures associated with the 2001 Central Kunlun earthquake: implications for the construction of the Qinghai–Tibet railway - Zeng Qingli; Ma Yinsheng; Zhao Yue; Yang Zhifa; Lin Aimin; Fu Bihong (Bulletin of Engineering Geology and the Environment, 2006)